The Impact of Resident Involvement on Postoperative Complications After Shoulder Arthroscopy: A Propensity-Matched Analysis. (September 2020) - Gulbrandsen, Trevor R.; Khazi, Zain M.; Shamrock, Alan G.; An, Qiang; Duchman, Kyle; Marsh, J. Lawrence; Westermann, Robert W.; Wolf, Brian
Abstract : Purpose: Shoulder arthroscopy is the second most frequently performed procedure by orthopaedic surgeons taking the American Board of Orthopaedic Surgery part II examination. However, the impact of resident involvement on outcomes after shoulder arthroscopy is poorly understood. The aim of this study was to investigate whether resident involvement in shoulder arthroscopic procedures affects postoperative complication rates and surgical time using propensity score-matched cohorts. Methods: The American College of Surgeons National Surgical Quality Improvement Program registry was queried to identify patients who underwent common shoulder arthroscopic procedures between 2006 and 2012. Cases without information on resident involvement, treatment of septic arthritis or osteomyelitis of the shoulder, or concomitant open or miniopen procedures were excluded from the study. A 1:1 propensity score match was used based on demographic and comorbidity factors to match cases with resident involvement to nonresident cases. Patient demographics, comorbidities, surgical time, length of hospital stay, and 30-day postoperative complications were compared between the two groups. Results: Overall, 15, 857 patients who underwent shoulder arthroscopy were identified. After propensity score matching, 3474 cases (50% with resident involvement) were included. Appropriate matching was verified with no difference in demographic or health characteristics. No significant differences in the overall rate of 30-day complications was noted in resident-involved versus nonresident group ( P = 0.576). No significant difference was observed in postoperative surgical or medical complications. Resident involvement was significantly longer surgical time (75.9 ± 35.9 versus 75.1 ± 40.5 minutes, P = 0.03) when compared with cases performed without a resident. Conclusions: Resident involvement in shoulder arthroscopy is not associated with increased risk for medical or surgical 30-day postoperative complications. Resident participation in shoulder arthroscopy cases did increase surgical time; however, this finding is likely clinically insignificant.